Experimental Investigation on Fluid Dynamic and Thermal Behavior in Confined Impinging Round Jets in Aluminum Foam. (November 2016) - Manca, Oronzio; Cirillo, Luca; Nardini, Sergio; Buonomo, Bernardo; Ercole, Davide
Abstract: In this paper an experimental investigation is carried out on impinging jets in porous media with the wall heated from below with a uniform heat flux. The fluid is air. The experimental apparatus is made up of a fun systems, a test section, a tube, to reduce the section in a circular section. The tube is long 1.0 m and diameter of 0.012 m. The test section has a diameter of 0.10 m and it has the thickness of 10, 20 and 40 mm. In the test section the lower plate is in aluminum and is heated by an electrical resistances whereas the upper plate is in Plexiglas. The experiments are carried out employing aluminum foams with 5, 10 and 40 PPI and three thickness over the heated circular plate. Results are obtained in a Reynolds number range from 500 to 1500 and wall heat flux from 500 W/m2 to 1400 W/m2. Results are given in terms of wall temperature profiles, local and average Nusselt numbers, pressure drops, friction factor and Richardson number. Moreover, to evaluate the improvement due to the presence of the metal foam, it is necessary a quantitative methodology. In this work an energy performance ratio is employed to compare the performances of surface with and without foams in terms of heat transfer coefficients and pressure drops. Preliminarily experimental results has confirmed that the use of the porous medium improves the heat transfer promoting the heat dissipation of the surface with high efficacy but determines an increase in pressure drops.